Acute submaximal exercise does not impact aspects of cognition and BDNF in people with spinal cord injury: A pilot study - Nhan, Keegan; Todd, Kendra R.; Jackson, Garett S.; Van der Scheer, Jan W.; Dix, Gabriel U.; Martin Ginis, Kathleen A.; Little, Jonathan P.; Walsh, Jeremy J. (Frontiers in Rehabilitation Sciences, 2022)
Objective: To investigate the effect of acute submaximal exercise, based on the spinal cord injury (SCI) Exercise Guidelines, on cognition and brain-derived neurotrophic factor (BDNF) in people with SCI. Design: Eight adults (7 males) with traumatic SCI volunteered in this pre-registered pilot study. In randomized order, participants completed submaximal intensity arm cycling (60% of measured peak-power output at 55-60 rpm) for 30 minutes or time-matched quiet rest (control condition) on separate days. Blood-borne BDNF was measured in serum and plasma at pre-intervention, 0 min and 90 min post-intervention. Cognition was assessed using the Stroop Test and Task-Switching Test on an electronic tablet pre- and 10 min post-intervention. Results: Submaximal exercise had no effect on plasma (F(2,12)=1.09; P=0.365; η²=0.069) or serum BDNF (F(2,12)=0.507; P=0.614; η²=0.024) at either 0 min or 90 min post-intervention. Similarly, there was no impact of exercise on either Stroop (F(1, 7)=2.05; P=0.195; η²=0.065) or Task-Switching performance (F(1, 7)=0.016; P=0.903; η² < 0.001) compared to the control condition. Interestingly, there was a positive correlation between years since injury and resting levels of both plasma (r = 0.831; P = 0.011) and serum BDNF (r = 0.799; P = 0.023). However, there was not relationship between years since injury and the BDNF response to exercise. Conclusions: Acute guideline-based exercise did not increase BDNF or improve aspects of cognition in persons with SCI. This work establishes a foundation for continued investigations of exercise as a therapeutic approach to promoting brain health among persons with SCI.